New Kids on the Unblocking: Strategies to Overcome Blocking Networks - Morais, Caio Von Rondow; Penha, Jeronimo; Nacif, José A.; Ferreira, Ricardo (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD), 2023)
Full-crossbar interconnections offer high parallel bandwidth, simple routing, and performance. However, their cost is prohibitive. Multistage networks have emerged as a cost-effective alternative, reducing the cost to O(n log(n)). This study addresses the challenges posed by large networks with 256 connections, where the configuration space expands exponentially. We present an approach that efficiently handles routing by reducing the extra stages. We reduce network cost by a factor of 2×. Our approach enables graph routing with up to 214 operators within the 256-connection multistage network, doubling performance compared to previous multistage CGRA frameworks.